Racial differences in the associations between adiposity, placental growth hormone and inflammatory cytokines in pregnant women - Williams, Camille Y.; Wylie, Amanda; Ghobrial, Verina; Coe, Christopher L.; Short, Sarah J. (Frontiers in Endocrinology, 2023)
The prevalence of obesity among women of child-bearing age has contributed to an increased risk of pregnancy complications with a disproportional impact on women of lower socioeconomic status and among certain racial groups. In particular, socio-demographic and historical factors have resulted in higher rates of premature births and small-for-gestational age infants among Black women, which may be associated with placental function during pregnancy. The current study investigated the influence of maternal pre-pregnancy adiposity and race on the associations between inflammatory proteins, placental growth hormone (PGH), and infant birthweight. This information was collected for a subsample of 109 participants (Black, n = 39 vs. White, n = 70) from the Brain and Early Experiences (BEE) study. Serum samples were acquired late in the second trimester to assess PGH levels, C-reactive protein (CRP), interleukin 6 (IL-6), interleukin 8 (IL-8), and interleukin-1 receptor antagonist (IL-1ra). Participant questionnaire responses provided information on pre-pregnancy BMI, health, race, educational attainment, and infant birthweight. Bivariate correlations and multiple linear regression models were utilized to evaluate associations by race between preconception adiposity, inflammatory markers and PGH. After controlling for covariates including maternal age and education, gestational age, and fetal sex, regression models indicated that pre-pregnancy BMI was negatively associated with PGH (β=-0.42, p<0.05) and IL-8 was positively associated with PGH (β=0.35, p<0.05) among the Black mothers only; neither were significantly associated with PGH in the White mothers. When extending models to birth outcomes, BMI was positively associated with birthweight corrected for gestational age (BWz) (β=0.24, p<0.05) and educational attainment was negatively associated with BWz (β=0.28, p<0.05) for infants of White women. In contrast, neither variable was predictive of BWz for infants of Black mothers. Future work is needed to investigate racial differences in the association between adiposity and placental functioning, which are likely to contribute to differential effects on pregnancy outcomes and fetal growth.